Migrasi Radio Konvensional menjadi Radio Digital - Salman Aditya Rahman Santoso; Santi Indra Astuti (UNISBA Press, 2024)
Abstract. The digitalization process in the radio broadcasting industry has made radio easy to access and consume by loyal radio listeners. Digital radio is a new trend among broadcasters and even beginners in this field, starting from various social media to applications focused on radio broadcasting have begun to develop features to make it easier for people to produce their works in this field. This research discusses how Media Convergence is implemented on 24Station campus radio. This research aims to find out how the migration of conventional radio to digital radio within the framework of media convergence in the 24Station radio community. This research explores the views of individuals and communities on the migration of campus radio to digital media. The study focuses on how they apply digital radio as a form of media convergence, based on their experiences in running programs for listeners. This research uses a qualitative approach as well as a case study method. The research subjects chosen were Ex-Kasie. Radio Laboratory, Radio Laboratory Ex-Labourer, Radio Laboratory Labourer and Radio Laboratory Assistant. The data collection techniques used were unstructured interviews and direct observation. The results of this study are that with all the migration processes, through existing regulations and policies, as well as the development mechanisms created, and the interaction patterns that exist, Radio 24Station still cannot be called a digital radio because it still uses web streaming radio, but Radio 24Station is in the process of digitizing radio and becoming a form of media convergence in the campus environment. Abstrak. Proses digitalisasi pada industri penyiaran radio membuat radio menjadi mudah untuk diakses dan dikonsumsi oleh para pendengar setia radio. Radio digital menjadi tren baru di kalangan para pegiat penyiaran bahkan pemula di bidang penyiaran ini, dimulai dari berbagai media sosial hingga aplikasi yang difokuskan pada bidang penyiaran radio sudah mulai mengembangkan fitur-fitur untuk memudahkan khalayak menghasilkan karya-karyanya di bidang ini. Penelitian ini membahas mengenai bagaimana Konvergensi Media diimplementasikan pada radio kampus 24Station. Penelitian ini bertujuan untuk mengetahui bagaimana migrasi radio konvensional menjadi radio digital dalam kerangka konvergensi media pada komunitas radio 24Station. Penelitian ini mengeksplorasi pandangan individu dan komunitas terhadap migrasi radio kampus ke media digital. Studi ini fokus pada bagaimana mereka mengaplikasikan radio digital sebagai bentuk konvergensi media, berdasarkan pengalaman mereka dalam menjalankan program-program untuk pendengar. Penelitian ini menggunakan pendekatan kualitatif dan juga metode studi kasus. Subjek penelitian yang dipilih merupakan Eks-Kasie. Laboratorium Radio, Eks-Laboran Laboratorium Radio, Laboran Laboratorium Radio dan Asisten Laboratorium Radio. Teknik pengumpulan data yang dipakai adalah wawancara tidak terstruktur dan observasi secara langsung. Hasil dari penelitian ini adalah dengan segala proses migrasi, melalui regulasi dan kebijakan yang ada, serta mekanisme pengembangan yang dibuat, dan juga pola interaksi yang terjalin, Radio 24Station masih belum bisa disebut sebagai radio digital karena masih menggunakan radio web streaming, akan tetapi Radio 24Station sedang dalam proses digitalisasi radio dan menjadi wujud konvergensi media pada lingkungan kampus.